1991
DOI: 10.1111/j.1360-0443.1991.tb01877.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school‐based drug education

Abstract: Outcome evaluation of the impact of drug education on a representative sample of 1197 pupils revealed no effects of drug education on drug-related behaviour or drug-related attitudes. However, drug education raised levels of drug-related knowledge. The long term implications of these findings would require further study. Comparison of process and outcome measures indicated that, with the exception of knowledge, teachers' positive views of drug education were misplaced. Critical aspects of good practice are dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The use of both solvents and amphetamines also appears to be on the increase, albeit not to the same extent as cannabis (Balding, 1994). In contrast, Coggans et al, (1991) found that the use of Class A drugs by young people was less than 1% of the population sampled.…”
Section: Illicit Drugsmentioning
confidence: 77%
See 1 more Smart Citation
“…The use of both solvents and amphetamines also appears to be on the increase, albeit not to the same extent as cannabis (Balding, 1994). In contrast, Coggans et al, (1991) found that the use of Class A drugs by young people was less than 1% of the population sampled.…”
Section: Illicit Drugsmentioning
confidence: 77%
“…has also argued that drugs education should be based on the perceptions young people have of drugs issues and an analysis of their own needs. Coggans et al (1991) finding that drugs education sessions may have a positive impact on drug-related knowledge indicates that programmes can impact at some level. However, Coggans and Watson (1995) have argued that multi-media and multi-dimensional approaches are more likely to be effective than approaches based on a single and simple philosophy.…”
mentioning
confidence: 88%
“…Among the few studies previously available of drug education in British schools, Coggans et al [21] reported on an evaluation of drug education in Scotland. In a nationally representative crosssectional survey, they found knowledge gains but no effect on attitudes or behaviour.…”
Section: Does It Really Matter?mentioning
confidence: 98%
“…In the UK, similar sources of influence have been implicated and have been variously reviewed (see for example O'Connor, Best, Best and Rowley, 1997;Evans, Mallick and Stein, 1997;McGurk and Hurry, 1995;Blackman, 1996;Ives and Clements, 1996;Coggans et al, 1991;Miller and Plant, 1996).…”
Section: Introduction Children At Risk For Substance Abusementioning
confidence: 97%